Superantigens Methods and Protocols - Brosnahan, Amanda J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2016)
This volume combines protocols that encompass the true variety of investigation done on superantigens in the fields of microbiology, immunology, molecular biology, biochemistry, and cellular biology, with a strong focus on disease models utilized to determine the role of superantigens in human disease. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Thorough and cutting-edge, Superantigens: Methods and Protocols contains a detailed and wide breadth of subject coverage that any scientist, clinician, or industry professional interested in this field will find valuable.
Keywords: Medicine; Immunology; Biomedicine; Immunology; Electronic books